On the specifics of land disputes and problems of their jurisdiction - Skobelev, Vladimir P.; Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the land disputes specificity based on material norms, some reasons for their emergence, conditioned by historical peculiarities of the formation and development of the land legislation of the Republic of Belarus and the practice of its application. Attention is also paid to the problems of jurisdiction of land disputes to courts, in particular, disputes over the violation of the boundaries of land plots and cases on establishing the long possession period for land plots. On this basis, some recommendations have been made to improve domestic law enforcement practice.
Keywords: land disputes; material and procedural features of land disputes; jurisdiction of land disputes; civil legal proceedings; violation of the boundaries of the land plot; long possession period of land plots